Behavioral misuse among clients in substance abuse treatment: an interview study. (3rd May 2016) - Punzi, Elisabeth; Tidefors, Inga; Fahlke, Claudia
Abstract: Background : The co-occurrence of substance misuse and behavioral misuse such as excessive food intake, sexual activities, gambling and exercise has been increasingly acknowledged in both research and treatment practice during the last decades. It has also been showed that behavioral misuse complicates substance abuse treatment, and that clients with such co-occurring difficulties have considerable treatment needs. Methodology : This study is based on interviews with six clients in substance abuse treatment, who also had a history of behavioral misuse. The interviews concerned the participants' perception of their behavioral misuse and of themselves, and were analyzed using interpretative phenomenological analysis. Findings and clinical implications : The participants perceived behavioral misuse as an escape from self-criticism and experiences of non-coherence. They also perceived relations and affects as overwhelming. Through behavioral misuse, relational and affective needs, as well as distressing self-experiences, were mitigated. The participants also described the efforts they had made to comprehend themselves. Their experiences were interpreted with respect to dissociation and concretization. It is suggested that during treatment, practitioners need to support client's comprehension and their capacity to approach affects and relational needs, and in this process, dissociation and concretization need to be handled.